Universal Legal Maxims on Mu’amalah Contracts from the Perspective of Sharia Economic Law - Enang Hidayat; Dadan Dadan (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2026)
This paper explores the thought of Shah Wali Allah al-Dihlawi on his concept of Universal Legal Maxims (qawa’id kulliyah), focusing not only on his inductive reasoning in Islamic jurisprudence but also on his philosophical approach to Islamic legal theory. The objective of this study is to explain Shah Wali Allah al-Dihlawi’s qawa’id kulliyah as presented in his seminal work “Hujjah Allah al-Balighah”, particularly in relation to mu’amalah (transactional contracts), and to analyze the philosophy of Islamic economic law in light of these principles. This research employs a normative, conceptual, and philosophical approach. The findings of this study reveal that al-Dihlawi presents seven qawa’id kulliyah in “Hujjah Allah al-Balighah”. Through these seven legal maxims, al-Dihlawi attempts to integrate his philosophical and mystical thought into various forms of mu’amalah contracts. The analysis of Islamic economic legal philosophy regarding these seven Kaidah Kulliyah aims at achieving public welfare (maslahah 'ammah), with a central focus on the protection of wealth—an objective that is implicitly embedded in several types of mu’amalah contracts, including mubadalah (exchange), ulfah (harmonious relations), muwasah (compassionate sharing), mu’awanah (mutual assistance), and mudayanah (deferred payment contracts). These contracts are driven by two main motives: fulfilling basic human needs and attaining public welfare both in this world and the hereafter. This study contributes to the enrichment of normative and philosophical approaches in constructing an adaptive and contextual framework for Islamic economic law.